1997
DOI: 10.1093/ajcn/65.3.761
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose polyester does not inhibit gastric acid secretion or stimulate cholecystokinin release in men

Abstract: Replacement of dietary lilt by sucrose polyester reduces fat intake. However, little is known about the effccts of sucrose polyester on gastrointestinal function. To investigate the effect on gastric acid secretion and on release of cholecystokinin into plasma, we perfused eight healthy male volunteers intraduodenally with sucrose polyester, digestible fat, or saline on separate days in random order, Intraduodenal perfusion of sucrose polyester did not suppress gastrin-stimulated gastric acid secretion ( -1.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 56 publications
(53 reference statements)
1
4
0
Order By: Relevance
“…Thus, substitution of chips made with olestra for chips cooked with conventional oils reduced the occurrence of postprandial gastro‐oesophageal reflux. These results are consistent with a lower production of serum CCK after the olestra meal, 30 because CCK is implicated in reducing lower oesophageal sphincter pressure.…”
Section: Structure and Function Of The Gastrointestinal Tractsupporting
confidence: 85%
“…Thus, substitution of chips made with olestra for chips cooked with conventional oils reduced the occurrence of postprandial gastro‐oesophageal reflux. These results are consistent with a lower production of serum CCK after the olestra meal, 30 because CCK is implicated in reducing lower oesophageal sphincter pressure.…”
Section: Structure and Function Of The Gastrointestinal Tractsupporting
confidence: 85%
“…It has been suggested that CCK acts as a satiety agent for fat in humans, based on the observation that a blocker of the CCK receptor inhibits the satiating effect of intestinal fat [45]. Fat substitutes, however, do not release CCK [46], which may explain why satiety decreases.…”
Section: Satiety Signalsmentioning
confidence: 99%
“…We believe that with a shorter time interval the volume and weight effects rather than the energy content and macronutrient effects of the preload will be measured on appetite and energy intake. Another argument in favour of a 90 min time interval is that the digestion of regular amounts of carbohydrates and fats results in the largest differences after 60 ± 90 min in appetite-related physiological responses, such as CCK (Maas et al, 1997), insulin (Jenkins et al, 1987), glucose (Wolever et al, 1991;Jenkins et al, 1987) and diet-induced thermogenesis (Blundell et al, 1993;Visser et al, 1995).…”
Section: Designmentioning
confidence: 99%